Kenya - Poverty and Inequality Assessment : Executive Summary and Synthesis Report - World Bank (World Bank, 2012)
This assessment of poverty and inequality comes at an important juncture for Kenya. The December 2007 elections and subsequent pronouncements of the newly formed Grand Coalition have underlined the salience of these issues to ordinary Kenyans, and for policy makers. The violence in early 2008 highlighted the importance of addressing poverty and inequality as major goals in their own right, but also for instrumental reasons, as major goals in their own right, the persistent inequalities spark conflict, which is welfare reducing, and this conflict in turn will harm prospects for growth. The onset of the global credit crunch has also shown how poverty and public service delivery related vulnerabilities could be exacerbated by external shocks. Cumulatively, these factors underline the value of appropriate diagnostics about the patterns of poverty and inequality in informing public debates, strategies and actions to overcome exclusion from the benefits of growth and development in Kenya as well as designing policies to minimize the impact of the current global crisis.